Phosphorus(III)-Promoted 1,2-Boronate Migration and Application to Stereoselective gem-C,B-Glycosylation - He, Zhi-Tao (Synlett, 2022)
Modifications of glycosidic linkers are valuable in medicinal chemistry and natural-product synthesis. Whereas considerable attention has been paid to the development of methods for monoglycosylation, the corresponding geminal diglycosylation has almost been ignored. Little work has focused on exploring new routes for stereoselective gem-diglycosylation, presumably due to challenges in controlling selectivity and activity on a confined quaternary carbon center. Highlighted herein is a recent advance in stereoselective C,B-glycosylation through an unprecedented PPh3-promoted 1,2-boronate-migration process.
Keywords: diglycosylation; boronate migration; phosphonium ylides; C,B-glycosylation; stereoselectivity